PENGARUH KREATIVITAS VERBAL TERHADAP SENSE OF HUMOR SISWA AKSELERASI - Ardhiana Puspitacandri (University of Merdeka Malang, 2013)
Good creativity is a requirement that students need to have accelerated in the selection process, factors other than intelligence. If the verbal creativity of its effect on one's sense of humor then students should have an individual acceleration humorous. Students are better able to look at the matter with a more comfortable and find many ways to resolve the problem. The population used in this study is that there are students in the MA acceleration Amanatul Ummah Surabaya. Sampling using simple random sampling. Results on the validity of verbal creativity test with a significance level of 0.05 moves from 0.337 to 0.700 while the sense of humor using a modified scale Multidimensional Sense of Humor with a validity of 0.90. Calculation of variable reliability alpha values ??obtained verbal creativity (?) = 0.918, and a sense of humor variable reliability values ??obtained alpha (?) = 0.70. Where two numbers are according to the rules stated reliability is very reliable on verbal creativity and reliable variable in the variable sense of humor. Results of data analysis showed no effect of verbal creativity to sense of humor of F = 7.965 and p = 0.007 (p 0.05)) then the working hypothesis stating no influence on verbal creativity in students a sense of humor acceleration (Ha) is accepted and correlation coefficient of 0.140